Infectious bursal disease virus affecting interferon regulatory factor 7 signaling through VP3 protein to facilitate viral replication - Wang, Zhiyuan; Chen, Yang; Chen, Yanyan; Chen, Rui; Wang, Weiwei; Hu, Shichen; Li, Yihai; Chen, Hongjun; Wei, Ping; He, Xiumiao (Frontiers in Cellular and Infection Microbiology, 2025)
Interferon regulatory factor 7 (IRF7)-mediated type I interferon antiviral response is crucial for regulating the host following viral infection in chickens. Infectious bursal disease virus (IBDV) is a double-stranded RNA virus that induces immune suppression and high mortality rates in chickens aged 3-6 weeks. Previous studies have shown that IBDV infection antagonizes the type I interferon production to facilitate viral replication in the cell, and IRF7 signaling might play an important role. However, the underlying mechanisms that enable IBDV to block the IRF7 pathway remain unclear. In this study, we found that IRF7 and IFN-β expression were suppressed in DF-1 cells during infection with very virulent IBDV (vvIBDV), but not with attenuated IBDV, while the virus continued to replicate. Overexpression of IRF7 inhibits IBDV replication while knocking down IRF7 promotes IBDV replication. Overexpression of IRF7 couldn’t compensate the IRF7 protein level in vvIBDV-infected cells, which suggested that IRF7 protein was degraded by IBDV infection. By using inhibitors, the degradation of IRF7 was found to be related to the proteasome pathway. Further study revealed that IRF7 was observed to interact and colocalize with the IBDV VP3 protein. Consistent with IBDV infection results, IBDV VP3 protein was observed to inhibit the IRF7-IFN-β expression, affect the degradation of IRF7 protein via proteasome pathway. All these results suggest that the IBDV exploits IRF7 by affecting its expression and proteasome degradation via the viral VP3 protein to facilitate viral replication in the cells. These findings revealed a novel mechanism that IBDV uses to evade host antiviral defense.